2020
DOI: 10.3390/forecast2030014
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Error Modeling to Improve GPM IMERG Precipitation Product over the Brahmaputra River Basin

Abstract: The Integrated Multisatellite Retrievals for Global Precipitation Measurement (GPM) (IMERG) Level 3 estimates rainfall from passive microwave sensors onboard satellites that are associated with several uncertainty sources such as sensor calibration, retrieval errors, and orographic effects. This study aims to provide a comprehensive investigation of multiple machine learning (ML) techniques (Random Forest, and Neural Networks), to stochastically generate an error-corrected improved IMERG precipitation product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 85 publications
(124 reference statements)
0
22
0
Order By: Relevance
“…Several merged SPDs (MSPDs) are developed across various regions of the globe and especially in Pakistan. Very recently, machine learning (ML) techniques have become popular in hydrological modeling, climate studies, water resources management [43,44], and precipitation sciences [45][46][47]. Different ML techniques have also been employed for merging different SPDs and SPDs with RGs.…”
Section: Introductionmentioning
confidence: 99%
“…Several merged SPDs (MSPDs) are developed across various regions of the globe and especially in Pakistan. Very recently, machine learning (ML) techniques have become popular in hydrological modeling, climate studies, water resources management [43,44], and precipitation sciences [45][46][47]. Different ML techniques have also been employed for merging different SPDs and SPDs with RGs.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation adds insights to refine strategies for combining IR and PMW precipitation estimates in the merged products such as IMERG. Therefore, this study is different from previous studies in which the final products of IMERG is assessed using ground reference [5][6][7]22]. Results of this study can improve future versions of satellite-based precipitation products and provide insight for new sensors' design and their performance over different conditions and regions.…”
Section: Introductionmentioning
confidence: 84%
“…These limitations lead to higher uncertainties in SREs performance over complex terrain [31]. On one hand, few studies [38][39][40] have highlighted the potential of machine learning (ML) based error characterization methods in quantifying and correcting SREs uncertainties over the complex terrain. Similarly, a study conducted in China suggested that blended product better facilitate the hydrological modeling by blending SREs, reanalyzing, and gauging data [41].…”
Section: Introductionmentioning
confidence: 99%